2020
DOI: 10.1177/1545968320969939
|View full text |Cite
|
Sign up to set email alerts
|

Agrin Involvement in Synaptogenesis Induced by Exercise in a Rat Model of Experimental Stroke

Abstract: Background Agrin is a proteoglycan that aggregates nicotinic acetylcholine receptors (AChRs) on neuromuscular junctions and takes part in synaptogenesis in the development of the central nervous system. However, its effects on neural repair and synaptogenesis after stroke are still unclear. Objective This study aimed to investigate the effects of agrin on neural repair and synaptogenesis after stroke and the effects of exercise on this process in vivo and in vitro. Methods Exercise with gradually increased int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Agrin plays an active role in re-innervation by promoting the recycling of AChRs at the motor endplate. As a consequence, exercise is associated with an upregulation of agrin at the NMJs [ 29 ]. Conversely, overexpression of neurotrypsin results in cleavage of agrin and reduced muscle strength and mass [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agrin plays an active role in re-innervation by promoting the recycling of AChRs at the motor endplate. As a consequence, exercise is associated with an upregulation of agrin at the NMJs [ 29 ]. Conversely, overexpression of neurotrypsin results in cleavage of agrin and reduced muscle strength and mass [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that deficits in TSP-1/2 lead to difficulty in recovery after cerebral ischemia mainly due to the role of these proteins on the formation of synapses and in axonal appearance. In addition, they also confirm that TSPs are partially secreted by astrocytes after the stroke, which was evidenced by the co-localization of TSP-1 and TSP-2 with S100 and GFAP, respectively (Liauw et al, 2008;Zhang et al, 2020).…”
Section: The Role Of Astrocytes In Synaptogenesis During Brain Damagementioning
confidence: 81%
“…The poststroke exercise improved the recovery of behavioral function and agrin played a critical role in the synaptogenesis process. Due to that, Agrin can be considered a potential therapeutic target for the treatment of stroke and other diseases of the nervous system ( Zhang et al, 2020 ).…”
Section: The Role Of Astrocytes In Synaptogenesis During Brain Damagementioning
confidence: 99%
“…Such properties provide tissues with resistance to deformation by high physical forces, as exemplified by aggrecan, the most important cartilage proteoglycan [ 79 , 86 , 95 , 96 ]. The proteoglycan family also includes compounds, such as syndecans (trans-membrane receptors; they bind numerous ligands present in the ECM, mediate signal transduction, cell adhesion, migration et al) [ 97 , 98 ], serglycin (the only known intracellular proteoglycan; found in leukocyte granules, regulates granulopoiesis) [ 99 , 100 , 101 ], perlecan and agrin (characteristic of the basement membrane, regulators of many cellular processes; agrin is involved in the formation of neuromuscular synapses) [ 102 , 103 , 104 , 105 , 106 , 107 ] and fibromodulin (involved in the collagen fibrillogenesis) [ 108 , 109 ].…”
Section: The Extracellular Matrix—composition Structure Functionsmentioning
confidence: 99%